1979
DOI: 10.2466/pr0.1979.44.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of Seriousness in Attempted Suicide: Significance of the MF Scale in Suicidal MMPI Profiles

Abstract: Survivors of suicide (184) were classified clinically into serious, ambivalent, and gesture pre-and post-suicidal states. It was noted that the MMPI profile interpretation concurs with this classification and shows the Masculinity-Femininity trend. The profile interpretation makes use of the individual interscale relationships and actuarial profiles. The relationship with the psychiatric clinical diagnostic category is also necessary. The MasculinityFemininity Scale is essential in MMPI profile interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Despite the general absence of cross-validated evidence, some (e.g., Farberow & Devries, 1967;Leonard, 1977;Sendbuehler et al, 1979) have concluded that various MMPI measures have the ability to identify high suicide risks. Despite the general absence of cross-validated evidence, some (e.g., Farberow & Devries, 1967;Leonard, 1977;Sendbuehler et al, 1979) have concluded that various MMPI measures have the ability to identify high suicide risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the general absence of cross-validated evidence, some (e.g., Farberow & Devries, 1967;Leonard, 1977;Sendbuehler et al, 1979) have concluded that various MMPI measures have the ability to identify high suicide risks. Despite the general absence of cross-validated evidence, some (e.g., Farberow & Devries, 1967;Leonard, 1977;Sendbuehler et al, 1979) have concluded that various MMPI measures have the ability to identify high suicide risks.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the eight studies of this type that are know t o us (Clopton & Jones, 1975;Farberow, 1950;Foster, 1975;Leonard, 1977;Ravensborg & Foss, 1969;Rosen, Hales, & Simon, 1954;Sendbuehler, Kincel, Nemeth, & Oertel, 1979;Simon & Gilberstadt, 1958), we found that 1 1 of the 13 standard M M P I scales-all but Lie and Hypomania-have been implicated as positive or negative suicide indicators. Three types of M M P I suicide-prediction research have appeared.…”
mentioning
confidence: 92%
“…However, most of the studies during this time period concluded that the MMPI was unable to differentiate between individuals who attempted or died by suicide and individuals with suicidal ideation alone or between individuals with or without suicidal ideation (Clopton & Baucom, 1979; Clopton & Jones, 1975; Clopton, Post, & Larde, 1983; Daigle, 2004; Kinsinger, 1973; Pallis & Birtchnell, 1977; Ravensborg & Floss, 1969; Sendbuehler, Kincel, Nemeth, & Oertel, 1979). …”
mentioning
confidence: 99%
“…Scant MMPI data was offered by the authors, and the overly inclusive criteria (threatening or attempting at any time in one's life) most certainly diminished any actual differences between groups. Sendbuehler, Kincel, Nemeth, and Oertel(1979) gathered MMPI data from 221 consecutive suicide attempters in danger of dying upon admission to a surgical unit. Valid MMPIs were obtained from 184 patients (127 female, 57 male) within 3 days of admission.…”
Section: Minnesota Multiphasic Personality Inventory (Mmpi)mentioning
confidence: 99%